Fishers and groupers (Epinephelus marginatus and E. morio) in the coast of Brazil: integrating information for conservation - Alpina Begossi; Svetlana Salyvonchyk; Branko Glamuzina; Shirley Pacheco de Souza; Priscila F. M. Lopes; Regina H. G. Priolli; Djalma Osmanir do Prado; Milena Ramires; Mariana Clauzet; Cleverson Zapelini; Daiana T. Schneider; Luis T. Silva; et al. (BMC, 2019)
Abstract Background Groupers are a vulnerable but economically important group of fish, especially for small-scale fisheries. We investigated catches and local ecological knowledge (LEK) of diet, habitat, and past fishing experiences. Methods Landings, prices, interviews, and restaurants demand for two species, Epinephelus marginatus (dusky grouper) and Epinephelus morio (red grouper), were registered. Results We visited 74 markets and 79 sites on the coast of Brazil in 2017-2018, and we interviewed 71 fishers: Bahia (NE), Rio de Janeiro and São Paulo (SE), and Santa Catarina (S). The landings sampled of dusky grouper (2016-2017) in Rio de Janeiro were: n = 222, size 38-109 cm, weight 1-24 kg, average 3.84 kg; in São Paulo, São Sebastião were: n = 47, size 39-106 cm, weight 2-8 kg, average of 2.77 kg; and at Santos: n = 80, 26-120 cm, weight 0.36-15 kg, average 2.72 kg. Red grouper was observed in markets in the northeastern Brazil. We did not observe Epinephelus marginatus from Bahia northward; a maximum size of 200 cm was reported south of the Bahia, besides Rio de Janeiro and São Paulo coasts, 20 years ago (or longer) by 12 fishers. Local knowledge of fishers was important for grouper data of habitat and diet; the reproduction period was identified by fishers as September to March. Conclusions Groupers can be considered as a cultural and ecological keystone species. We suggest protective measures: 1) fishing zoning, 2) islands (MPAs) with the surveillance of fishers, 3) late Spring and early Summer as key periods for management (grouper reproduction), 4) studies on grouper larvae, 5) mapping of fishing spots, 6) studies on local knowledge. Collaboration with small-scale fishers and local knowledge could contribute to low-conflict management measures. In that regard, integrative models of management from Latin America, by using local knowledge and citizen science, could produce successful grouper management for Brazilian data-poor fisheries, a contrasting reality to the Mediterranean areas. Finally, the distribution of E. marginatus in Brazil leave us with questions: a) Have dusky groupers disappeared from Bahia because of a decline in the population? b) Was it uncommon in Northeast Brazil? c) Did changes in water temperatures forced a movement southward?